PENGARUH LATAR BELAKANG ETNIS, KECERDASAN ADVERSITAS DAN REGULASI DIRI DALAM BELAJAR TERHADAP ORIENTASI WIRAUSAHA SISWA SMP NEGERI 31 SURABAYA - Wardayati, Setijo (UNIVERSITAS NEGERI SURABAYA, 2017)
This study aims to analyze the influence of ethnic background, adversity quotient and self-regulated learning of the students entrepreneurial orientation SMP Negeri 31 Surabaya. This study uses a quantitative approach. This research was conducted in class VII and VIII in SMP Negeri 31 Surabaya for academic year of 2014-2015 with population of 663 students. Sample was 249 students, selected by proportional random sampling. Data analysed using multiple regression analysis. The results showed there is positive and significant effect ethnic backgrounds, intelligence adversity and self-regulated learning of the students' entrepreneurial orientation SMP Negeri 31 Surabaya either partially or simultaneously. The influence of ethnic background, adversity quotient and self-regulated learning of the students' entrepreneurial orientation amounted to 63.8%, while the rest influenced by other factors not examined in this study.